Kinetics and Determining Factors of the Virologic Response to Antiretrovirals during Pregnancy - Adriana Weinberg; Jeri E. F. Harwood; Elizabeth J. McFarland; Jennifer Pappas; Jill Davies; Kay Kinzie; Emily Barr; Suzanne Paul; Carol Salbenblatt; Elizabeth Soda; Anna Vazquez; Charles A. Peloquin; et al. (Hindawi Limited, 2009)
HIV-infected pregnant women with undetectable plasma HIV RNA concentrations at delivery pose a minimal risk of vertical transmission. We studied the kinetics and the determinants of the virologic response to antiretroviral therapy in 117 consecutive pregnancies. Patients who initiated therapy during pregnancy had a VL decrease of 2 and 2.5 log10 after 4 and 24 weeks, respectively. Therapeutic drug monitoring (TDM) of the protease inhibitors administered in doses recommended for nonpregnant adults resulted in below-target concentrations in 29%, 35%, and 44% of 1st, 2nd, and 3rd trimester measurements, respectively, but low drug concentrations did not correlate with virologic failure. Demographic characteristics, antiretroviral experience prior to pregnancy, baseline VL, or use of specific antiretrovirals did not affect the virologic response. Adherence to ≥95% of prescribed doses and utilization of psychosocial services were associated with undetectable plasma HIV RNA at delivery. In conclusion, the virologic responses of pregnant and nonpregnant adults share similar charactersitics.